Adjustment of the water addition amount for barley batter based on the particle size effect aiming product development efficiency - Asuka Taniguchi; Makoto Miura; Tsuyoshi Tanaka; Rie Kobayashi (Discover Food)
Abstract Barley flours available on the market differ in particle size; thus, managing the rheological properties of the batter necessitates adjusting the water addition amount (WAA) during the production of barley flour products. This study explored how to change the WAA appropriately in such instances. To apply the results to various barley flour products, we tested three batter concentrations created by adding water at 3.00, 2.50, or 2.00 times the flour’s weight. Our findings showed that lowering the WAA for the large particle size batter (volume mean diameter, 270 µm) resulted in rheological properties similar to those of the small particle size batter (160 µm) across all concentrations. Additionally, we discovered that the required extent of WAA adjustment depended exponentially on the batter concentration, a significant outcome of this investigation. For lower batter concentrations, such as crepe batter, the adjustment in WAA related to particle size was under 1%, a minuscule figure. Conversely, for higher batter concentrations like cake batter, the adjustment was 5%. These outcomes imply that failing to adjust the WAA following particle size and product types could lead to considerable changes in the final product’s quality. We anticipate that our results will aid in estimating WAA adjustments in the actual manufacturing of barley flour products. Graphical abstract